Influence of equal-channel angular pressing on the corrosion fatigue behaviour of an Al-Mg-Si aluminium alloy for automotive conductors. (November 2020) - Rochet, C.; Andrieu, E.; Arfaei, B.; Harouard, J.-P.; Laurino, A.; Lowe, T.C.; Odemer, G.; Blanc, C.
Graphical abstract: Highlights: ECAP induced an increase in fatigue lifetime in air due to grain refinement. Pre-corrosion and corrosion fatigue led to a decrease in fatigue lifetime. A synergy between cyclic mechanical loading and corrosion processes was shown. IMC breakdown led to more corrosion defects and a decrease in fatigue lifetime. Higher sensibility to pre-corrosion and corrosion fatigue was found after ECAP. Abstract: The influence of equal channel angular pressing (ECAP) on the corrosion fatigue behaviour of an Al-Mg-Si alloy was studied. Preliminary fatigue tests in air showed an increase in fatigue lifetime for ECAP samples, as compared to as-received samples, related to the ECAP-induced grain refinement. After pre-corrosion, the fatigue lifetime was lower for ECAP samples than for as-received samples, because the fragmentation of coarse intermetallics during ECAP led to an increase in the density of corrosion defects. Corrosion fatigue tests demonstrated a synergy between cyclic mechanical loading and corrosion processes for all samples; a deleterious effect of ECAP was also noted.